Variation of healthcare associated infections at a tertiary hospital in Southwest China over a 5-year period (2019–2023): a retrospective observational study - Danyan Liang; Wei Liu; Yao Zhong; Jun yang; Lulin Chen (BMC Infectious Diseases)
Abstract Background Healthcare-associated infections (HAIs), which are associated with prolonged hospitalization and increased mortality, remain a global challenge. The COVID-19 pandemic paradoxically reduced some HAIs through enhanced hygiene measures but exacerbated others due to resource diversion, with effects after policy changes remaining unclear. Therefore, this study analyzed HAIs distribution, pathogenic microorganisms distribution, and antibiotic susceptibility capturing the period surrounding strict COVID-19 control measures in a southwest China tertiary hospital. Methods We conducted a retrospective study at a tertiary hospital in southwest China from 2019 to 2023. Data were extracted from real-time surveillance system, where HAIs were initially diagnosed by clinicians and subsequently verified by infection control personnel. The HAI incidence rate was calculated per 1000 hospital stays, and negative-binomial regression was used to compare incidence rates across years. Results This study enrolled 2808 HAI cases, with 1665 males and 1143 females, averaging 61.37 years old. The incidence rates of HAIs from 2019 to 2023 were 1.75, 1.12, 0.98, 1.31, and 1.30 per 1000 hospital stays, respectively. Hematology (323, 11.50%), cardiology (309, 11.00%), and neurology (262, 9.33%) were the top three departments with the highest HAI rates. Lower respiratory tract (1198, 42.66%), bloodstream (419, 14.92%), and urinary tract (406, 14.46%) were the most common HAI sites. Klebsiella pneumoniae (173, 15.22%), Escherichia coli (155, 13.63%), and Acinetobacter baumannii (136, 11.96%) were the most frequent pathogenic microorganism. Acinetobacter baumannii was resistant to most antibiotics. Klebsiella pneumoniae was most resistant to cefuroxime Axetil, cefuroxime and ceftriaxone. Escherichia coli was most resistant to sulfamethoxazole and trimethoprim, ceftriaxone and cefuroxime. These three pathogenic microorganisms were all susceptible to tigecycline. Conclusions The incidence rates of HAIs fluctuated over the years, peaking in 2019, suggesting potential shifts in infection control dynamics. Klebsiella pneumoniae, Escherichia coli, and Acinetobacter baumannii were the predominant pathogens, and tigecycline may be considered as a potential option against these pathogens. The study highlights the importance of enhancing infection control measures in high-risk departments and sites, optimizing antibiotic stewardship, and continuously monitoring HAI trends to inform evidence-based infection control policies. Clinical trial Not applicable.